Adjuvant chemotherapy could improve the survival of pulmonary sarcomatoid carcinoma: A systematic review and meta-analysis. (September 2022) - Zombori-Tóth, Noémi; Kiss, Szabolcs; Oštarijaš, Eduard; Alizadeh, Hussain; Zombori, Tamás
Abstract: Background: Complete surgical removal is currently considered to be the best treatment option for pulmonary sarcomatoid carcinoma (PSC) especially in early stage operable disease; however, the reported recurrence-free survival is low. Benefits of adjuvant chemotherapy in PSC patients are still controversial, and there is no obvious agreement on the optimal treatment modalities of this disease. Therefore, we aimed to investigate the prognosis in terms of overall survival (OS) in patients with PSC who received adjuvant chemotherapy. Methods: The review protocol was registered in PROSPERO (CRD42022306084). Patients with PSC who underwent surgical therapy with or without adjuvant chemotherapy were included into the meta-analysis. Hazard ratios (HR) with 95% confidence intervals (CIs) for OS were pooled and ROBINS-I tool was used to assess risk of bias of the included studies. Results: We identified four retrospective cohort studies with 6768 records from MEDLINE, Embase, and CENTRAL databases up to 9th September 2021, and altogether 1835 patients were included to the analysis. The present meta-analysis shows that patients receiving adjuvant chemotherapy had a significantly longer OS than patients who underwent surgical treatment alone (HR = 0.5657, 95%CI: 0.4391–0.7290, p < 0.0001). Conclusions: Despite the limited information on the chemotherapy regimens in the included studies, patients with PSC may benefit from adjuvant chemotherapy. More publications are required to evaluate and compare efficient adjuvant chemotherapy protocols in PSC cases. Highlights: The pulmonary sarcomatoid carcinoma (PSC) is a rare but aggressive tumour with low overall survival (OS) rate. Complete surgical removal is currently considered to be the best therapeutic management for PSC. Benefits of adjuvant chemotherapy in PSC patients are still controversial. This is the first meta-analysis evaluating the impact of the two therapeutic modalities on OS. Patients receiving adjuvant chemotherapy had a significantly longer OS than patients with surgical treatment alone.